Is location of sex associated with sexual risk behaviour in men who have sex with men? systematic review of within-subjects studies - Melendez-Torres, GJ; Nye, E; Bonell, C (Springer, 2015)
To understand associations between location of sex and sexual risk, it is most helpful to compare sexual encounters within persons. We systematically reviewed within-subjects comparisons of sexual encounters reported by men who have sex with men (MSM) with respect to location of sex. Within-subjects comparisons of sexual risk and location of sex were eligible if they collected data post-1996 from samples of MSM. We independently screened results and full-text records in duplicate. Of 6,336 deduplicated records, we assessed 138 full-text studies and included six, most of which compared unprotected anal intercourse against other anal intercourse. This small, but high quality, body of evidence suggests that associations between attendance at sex-on-premises venues and person-level sexual risk may be due to overall propensity towards unprotected sex. However, there may be some location factors that promote or are associated with serononconcordant unprotected anal intercourse. Health promoters may wish to focus on person-level characteristics.